Islamization of Natural Sciences - Zin Eddine Dadach (Indonesian Journal of Islamization Studies, 2024)
Islamic science, grounded in the Holy Quran and the Sunnah, thrived for over twelve centuries before facing cultural and civilizational crises in the early nineteenth century. By the early twentieth century, the decline peaked with the fall of the Ottoman sultanate and the division of Muslim lands by European powers. Modern Western civilization, shaped by the Renaissance and Enlightenment, prioritized scientific inquiry, empiricism, and freedom, but was also rooted in atheism, agnosticism, nihilism, and ethical relativism. This led to significant progress during the Industrial Revolutions. While the West celebrated scientific advancement, the Muslim world struggled to keep pace, resulting in an inferior position during interactions with the West. The 20th century introduced modern science to the Islamic world, facilitated by expanded education systems, such as the universities in Istanbul and Cairo established in 1900 and 1925. This led to challenges, including naturalism and social Darwinism, which conflicted with Islamic beliefs. Efforts to harmonize science with Islam resulted in diverse viewpoints among Muslim scholars. Nonetheless, the Muslim world’s scientific progress remains limited, as evidenced by low scientific output, research expenditures, and the number of researchers and engineers, highlighting concerns about contemporary scientific illiteracy.